TUTURAN KEPEMIMPINAN BASUKI TJAHAJA PURNAMA - Ria Andriani; Charlina '; Hermandra ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study titled Leadership speech Tjahaja Basuki Purnama. Research aims to determine speech Tjahaja Basuki Purnama. The method used in this research is descriptive method with qualitative approach. This research data is Basuki Tjahaja Purnama speech conversation with the society of honesty, courtesy, and interesting. Source of research data is a video leadership Basuki Purnama Tjahaja of seven video obtained from the site youtube. From this video obtained by the speech of leadership that has honesty, courtesy, and attractiveness. This study used a technique that documents the source data used to complete the study in the form of written sources, films or videos, pictures or photographs and monumental works dmemberikan information for the research process. The research found the data as much as seventy-four, consisting of (1) thirty Data honesty analyzed based on the language used, (2) thirty-two data is courtesy were analyzed based on the language used, and (3) the attractiveness of the analyzed based on the language used.Key words: Leadership speech, Basuki Tjahaja Purnama.